Constraints on global symmetry breaking in quantum gravity from cosmic birefringence measurements - James Alvey (Elsevier, 2021)
All global symmetries are expected to be explicitly broken by quantum gravitational effects, and yet may play an important role in Particle Physics and Cosmology. As such, any evidence for a well-preserved global symmetry would give insight into an important feature of gravity. We argue that a recently reported 2.4σ detection of cosmic birefringence in the Cosmic Microwave Background could be the first observational indication of a well-preserved (although spontaneously broken) global symmetry in nature. A compelling solution to explain this measurement is a very light pseudoscalar field that interacts with electromagnetism. In order for gravitational effects not to lead to large corrections to the mass of this scalar field, we show that the breaking of global symmetries by gravity should be bounded above. Finally, we highlight that any bound of this type would have clear implications for the construction of theories of quantum gravity, as well as for many particle physics scenarios.